Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1159/000346322
|View full text |Cite
|
Sign up to set email alerts
|

Salvage <sup>125</sup>I Seed Implantation for Prostate Cancer with Postradiation Local Recurrence

Abstract: Introduction: Although radiotherapy has been important in the therapy for localized prostate cancer, prostate-specific antigen failure may occur. This study evaluated the effects and side effects of 125I low-dose-rate brachytherapy for patients with postradiation local failure. Patients and Methods: 15 patients who received salvage brachytherapy were analyzed. A prescribed dose of 144 Gy was selected. Median follow-up calculated from the date of salvage brachytherapy was 33.0 months (range 6-51). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Stratifying patients based on PSA kinetics may help predict the likely response to salvage brachytherapy. The PSA nadir post salvage was identified as a predictor of bPFS in previous studies [8,22,24,32]. This is consistent with the results of our study, where nadir PSA < 0.2 ng/ml was associated with improved bPFS post salvage.…”
Section: Discussionsupporting
confidence: 92%
“…Stratifying patients based on PSA kinetics may help predict the likely response to salvage brachytherapy. The PSA nadir post salvage was identified as a predictor of bPFS in previous studies [8,22,24,32]. This is consistent with the results of our study, where nadir PSA < 0.2 ng/ml was associated with improved bPFS post salvage.…”
Section: Discussionsupporting
confidence: 92%
“…Only one patient experienced grade 3 rectal hemorrhage, while others experienced grade 2 complications that were managed conservatively. A similar study of 15 patients, who underwent brachytherapy for the treatment of recurrence after definitive EBRT, showed a biochemical relapse-free survival rate of 60.2% 3 years after salvage brachytherapy and all acute adverse events were grade 1 or 2 (12). Furthermore, Ramey and Marshall (15) investigated 18 previous studies of salvage brachytherapy and concluded that brachytherapy is a reasonable salvage option for patients with local recurrence after primary EBRT for prostate cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Salvage re-irradiation for recurrent prostate cancer after primary EBRT has been limited due to toxicity to adjacent organs, particularly the rectum and bladder (10). Although, certain recent studies have reported the effectiveness and safety of re-irradiation with brachytherapy for locally relapsed prostate cancer, reports of re-irradiation using EBRT are scarce (11,12). Thus, in the present study, two cases of locally relapsed prostate cancer following EBRT treated with re-irradiation using helical tomotherapy are discussed.…”
Section: Introductionmentioning
confidence: 92%
“…A recent systematic review by the Reirradiation Study Group of the Italian Association of Radiation Oncology (AIRO) showed that salvage brachytherapy is the most commonly used radiation technique for post-EBRT intraprostatic tumor recurrence [31]. Brachytherapy allows delivery of high doses to the target volume with remarkable OAR sparing in view of a rapid dose fall-off outside the sources, and more and more experiences have been published on this [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51], so that it is recommended by NCCN guidelines, too. Some other reports describe prostate stereotactic Re-I using the Cyber Knife [52][53][54][55][56][57], or external beam Re-I with VMAT [14,15,58,59].…”
Section: Discussionmentioning
confidence: 99%